Prevalence of Prediabetes, Diabetes, and Its Associated Risk Factors among Males in Saudi Arabia: A Population-Based Survey - Khaled K. Aldossari; Abdulrahman Aldiab; Jamaan M. Al-Zahrani; Sameer H. Al-Ghamdi; Mohammed Abdelrazik; Mohammed Ali Batais; Sundas Javad; Shanila Nooruddin; Hira Abdul Razzak; Ashraf El-Metwally (Journal of Diabetes Research)
Objectives. The study aims at determining the prevalence of prediabetes and diabetes and at ascertaining some concomitant risk factors among males in Saudi Arabia. Methods. A population-based cross-sectional study including 381 Saudi adult males from different institutions was recruited. Odds ratios for diabetes risk and risk factors were calculated using log-binomial and multinomial logistic regression, using STATA version 12. Results. The participants included 381 diabetic males with a median age of 45 years, average body mass index of 25 ± 40 kg/m2, whereas waist circumferences ranged from 66 to 180 cm in the male study population. In addition, 27.82% had normal BMI, 32.28% were overweight, and 36.22% were obese. Around 36% had higher waist circumference, that is, >102 cm. Age, BMI, marital status, and educational attainment were statistically significant predictors for prediabetes and diabetes. Conclusion. This study found that the prevalence of diabetes and prediabetes was 9.2% and 27.6%, respectively, for male Al-Kharj study population. The factors that increase the risk of diabetes and prediabetes include older age, obesity and overweight, being married, smoker, and having a civilian job and less education. All these factors were found statistically significant except smoking status and job type. In order to evaluate the causal relationship of these factors, prospective studies are required in future.